EFFECTIVENESS OF ELEOVIT PREPARATION WITH TISSUE PREPARATIONS IN CALVES - Abror Azamovich Khalikov; Nurullaev Alisher Abdullaevich; Khatamov Tolmas Tolkinovich; Omonov Shohzod Kakhramon Ugli (Galaxy International Interdisciplinary Research Journal, 2021)
The use of the vitamin preparation eleovit and tissue preparations in the diet of calves optimizes metabolic processes, contributing to the efficient use of feed. Increases productivity and increases live weight gain by 20.3%.